A.2 Proofs for Chapter 5 — Linearizing Completion 247
then a derivation
D
0
=(L ⇒
∗
(J\{P →C})
g
L
0
)
exists with D
0
≺ D.
Proof. Informally: if P
0
→ C
0
is deleted in J then it must be c-redundant in
I. By redundancy, the use of P
0
→ C
0
in any derivation D
0
can be simulated
by the remaining rules of I. However, that simulating derivation, say D
00
might use P → C, which should not be used according to the lemma. On
the other hand, P → C itself is given as c-redundant in I and hence can be
simulated by the remaining rules. However, that derivation, say D
000
possibly
contains usages of P
0
→ C
0
again. Continuing this process will not fall into
a loop due to strictly reduced complexity (D
000
≺ D
00
≺ D
0
) in every new
derivation and well-foundedness of .
Now the formal proof: if P → C/∈Ithen the lemma holds trivially by
the definition of -c-redundancy.
Otherwise we apply well-founded induction on derivation orderings.
With I\{P
0
→ C
0
}⊆Iit follows D =(L ⇒
∗
I
g
L
0
). With P
0
→ C
0
being deleted from I, P
0
→ C
0
must have been -c-redundant in I.Weare
given that a ground instance of P
0
→ C
0
is used in D. Hence by definition of
-c-redundancy a derivation
D
0
=(L ⇒
∗
(I\{P
0
→C
0
})
g
L
0
) (A.55)
exists with D
0
≺ D. Now we distinguish two cases:
Case 1: No ground instance of P → C is used in D
0
. But then by the
existence of D
0
we find with (A.55) that D
0
=(L ⇒
∗
((I\{P →C})\{P
0
→C
0
})
g
L
0
),
which proves the lemma.
Case 2: A ground instance of P → C is used in D
0
. First note that from
I\{P
0
→ C
0
}⊆Iby (A.55) it follows D
0
=(L ⇒
∗
I
g
L
0
). We are given that
P → C is -c-redundant in I. By definition of -c-redundancy we conclude
that a derivation D
00
=(L ⇒
∗
(I\{P →C})
g
L
0
) exists such that D
00
≺ D
0
(≺ D).
Now apply the induction hypothesis to D
00
and conclude the result from
transitivity of .
Lemma 5.4.3. Let S be a transformation system with derivation ordering
.LetI
0
`I
1
`··· be a S-deduction. If for some k, P → C is -c-redundant
in I
k
then P → C is -c-redundant in I
∞
.
Proof. In order to prove the lemma suppose that
D =(L ⇒
∗
(I
∞
∪{P →C})
g
,M
L
0
) (A.56)
which uses a ground instance of P → C. We have to show that a derivation